Labouring and Learning in Nineteenth-Century Canada: Children in the Changing Process of Family Reproduction - Gaffield, Chad (Université d'Ottawa | University of Ottawa, 1991)
in Russell Smandych, Gordon Dodds, and Alvin Esau, eds., Dimensions of Childhood: Essays on the History of Children and Youth in Canada (Winnipeg, Manitoba: Legal Research Institute, 1991): 13-27